اعادة تهيئة محيط منارة "كاب إيفي" - صندوق, فاطمة; نابي, حفصة (كلية الأدب العربي والفنون, 2024)
تهدف هذه الدراسة الى إعادة تهيئة محيط منارة كاب إيفي بإعطاء تصور نموذجي إبداع متميز يتمثل في مشروع اقتصادي سياحي ترفيهي خدماتي يتوفر على كل شروط الترفيه المتميزة المواكبة للعصر تمثلت في مطعم و مختلف فضاءات الراحة واللعب .إذا بمشروعنا هذا وبتصورنا هذا إن وجد على أرض الواقع أو كتب له التحقيق قد يكون مشروعا هندسيا متميزا ذو بصمة إبداعية محلية بكفاءات وطنية وبإرادة شبابية قد يثري القطاع السياحي بالجزائر أو بمنطقة أخرى قد يقصدها الألاف من الزوار داخل وخارج الوطن خاصة عشاق السياحةالتاريخيةومحبي هذا النوع من السياحة .والتي بإمكانها أن تحدث قفزة نوعيه في هذا السياحةبالمنطقة ولعل منطقة "كاب إيفي" إحدى أهم المناطق التي قد يساهم التنمية فيها وتحديث المنشآت ومواكبة العصر بها This study aims to redevelop the surroundings of the Cape Ivi lighthouse by providing a unique and creative model for an economic, tourist, recreational, and service project that meets all the requirements of modern distinguished entertainment. This is represented by a restaurant and various relaxation and play areas. If our project and our vision are implemented on the ground or are achieved, it could be a distinguished engineering project with a local creative touch, using national expertise and the will of young people. It could enrich the tourism sector in Algeria or in another region that could be visited by thousands of visitors from within and outside the country, especially lovers of historical tourism and fans of this type of tourism. This project could make a qualitative leap in this type of tourism in the region. Cape Ivi is one of the most important areas that could contribute to its development, modernization of its facilities, and keeping up with the times.
Keywords: منارة , إعادة التهيئة , سياحة تاريخية , سياحة شاطئية , معالم تاريخية; Lighthouse , Redevelopment , Historical tourism , Beach tourism , Historical landmarks